THE EFFECT OF PSAK 71 COMPARED TO PSAK 55 ON NET PROFIT, CAR, AND LDR IN BANKING COMPANIES IN INDONESIA - Herjanto, Celina Angeline; Bimo , Irenius Dwinanto (Universitas Katolik Indonesia Atma Jaya, 2025)
The implementation of PSAK 71 has been effective since January 1, 2020, replacing PSAK 55. The primary difference between the two standards lies in the calculation method for the Allowance for Impairment Losses, where PSAK 71 adopts the expected credit loss (ECL) model, which is more proactive than the loss incurred model (LIM) applied in PSAK 55. This study aims to analyze the differences in net profit, capital adequacy ratio (CAR), and loan-to-deposit ratio (LDR) in 46 banking companies in Indonesia during the 2019–2021 period. Secondary data were used, and the analysis was conducted using SPSS. While the initial analysis applied the paired sample t-test, the Shapiro–Wilk normality test indicated that all variables were not normally distributed; therefore, the Wilcoxon signed-rank test was employed. The results reveal that net profit differs significantly between 2019 and 2020, but shows no significant difference between 2019 and 2021. CAR does not differ significantly between 2019 and 2020, but differs significantly between 2019 and 2021. LDR shows no significant differences in both year-to-year comparisons. These findings indicate that the impact of PSAK 71 varies across financial indicators, with the strongest effect observed on net profit during its first year of implementation.